Second-Order Ambiguity in Very Low Probability Risks: Food Safety Valuation - Paul A. Kivi; Jason F. Shogren (Journal of Agricultural and Resource Economics, 2010)
Food consumption involves inherently risky decisions with uncertain probabilities. This study examines how second-order ambiguity, or uncertainty over probabilities, affects food safety decisions. We conduct a food safety survey wherein subjects face both unambiguous and ambiguous situations, each with the same expected value. Respondents show a preference for unambiguous situations and state a willingness to pay to avoid ambiguity